Characteristics of clinical manifestations and therapeutic approaches in pediatric allergic diseases - Tekwani, V.; Varahabhatla, V. (Запорізький державний медичний університет, 2017)
Introduction: One of the most important problems of dermatology is the treatment of allergic skin diseases. An alternative method of topical treatment that has served topical and systemic side effects is the use of herbal remedies, such as products based on plants Cardiospermum halicacabum. Aim: To determine the efficacy and safety of an integrated treatment of allergic skin diseases using topical products based on plants Cardiospermum halicacabum compared to standard therapies with changes of microbiota skin.
Keywords: тези